(untitled) - Wade, L. G (New Jersey, 2006)
Wade, organized around functional groups, is known for his student-oriented approach--he incorporates problem solving help (features in green), orientation features (in blue), and complete discussions of mechanisms (mechanism boxes and key mechanism spreads). As always, he explains concepts without taking the unnecessary short cuts that often lead to misconceptions. Additionally, he integrates up-to-date aspects of spectroscopy, bioorganic chemistry (often through accessible margin notes), and many applications to polymer chemistry throughout.
Anh văn chuyên môn - Hóa học
Keywords: Chemistry organic